LTβR signalling preferentially accelerates oncogenic AKT-initiated liver tumours. Issue 10 (23rd July 2015) - Scarzello, Anthony J; Jiang, Qun; Back, Timothy; Dang, Hien; Hodge, Deborah; Hanson, Charlotte; Subleski, Jeffrey; Weiss, Jonathan M; Stauffer, Jimmy K; Chaisaingmongkol, Jitti; Rabibhadana, Siritida; Ruchirawat, Mathuros; et al.
Abstract : Objectives: The relative contributions of inflammatory signalling and sequential oncogenic dysregulation driving liver cancer pathogenesis remain incompletely understood. Lymphotoxin-β receptor (LTβR) signalling is critically involved in hepatitis and liver tumorigenesis. Therefore, we explored the interdependence of inflammatory lymphotoxin signalling and specific oncogenic pathways in the progression of hepatic cancer. Design: Pathologically distinct liver tumours were initiated by hydrodynamic transfection of oncogenic V-Akt Murine Thymoma Viral Oncogene Homolog 1 (AKT)/β-catenin or AKT/Notch expressing plasmids. To investigate the relationship of LTβR signalling and specific oncogenic pathways, LTβR antagonist (LTβR-Fc) or agonist (anti-LTβR) were administered post oncogene transfection. Initiated livers/tumours were investigated for changes in oncogene expression, tumour proliferation, progression, latency and pathology. Moreover, specific LTβR-mediated molecular events were investigated in human liver cancer cell lines and through transcriptional analyses of samples from patients with intrahepatic cholangiocarcinoma (ICC). Results: AKT/β-catenin-transfected livers displayed increased expression of LTβ and LTβR, with antagonism of LTβR signalling reducing tumour progression and enhancing survival. Conversely, enforced LTβR-activation of AKT/β-catenin-initiated tumours induced robust increases in proliferation and progression of hepatic tumour phenotypes in an AKT-dependent manner. LTβR-activation also rapidly accelerated ICC progression initiated by AKT/Notch, but not Notch alone. Moreover, LTβR-accelerated development coincides with increases of Notch, Hes1, c-MYC, pAKT and β-catenin. We further demonstrate LTβR signalling in human liver cancer cell lines to be a regulator of Notch, pAKTser473 and β-catenin. Transcriptome analysis of samples from patients with ICC links increased LTβR network expression with poor patient survival, increased Notch1 expression and Notch and AKT/PI3K signalling. Conclusions: Our findings link LTβR and oncogenic AKT signalling in the development of ICC.